Cartographic Map Abstraction Using R Programming (Literacy Rate, HDI and Poverty Data Interpolation of Nepal) - Yagyanath Rimal; Sakuntala Pageni (Research Parks Publishing LLC, 2019)
R programming with map data interaction is another research area for data scientists due to high data publication in modern electronic records web applications at the federal administrative structure of Nepal. However the analysis of map and its presentation on web with interactively with data interperation has not much concern with data scientist while website design around the world. The data like central, province, local administrative government bodies many times published data for civil concerned. The dynamic records presentation with local boundaries map having interactive facilities has a new concept using r programming. Here the researcher could easily have developed the local administrative map using GIS shapefile then local level records generally gathered and stored in ms excel will automatically be integrated with this template easily so that local administrative agencies will easily update web site using r programming i.e rpubs. Which discards the registration domain, and knowledge of web application design intelligent site. The best application of this type of data interactive map with data interoperation would be highly applicable to local governance of Nepal where there was a large type of data and records that were developed in sequential order for public concern. The interactive VDC, district, province data commonly highlights data like, education rates and HDI information of any location that could easily be published. The developed model is available (http://rpubs.com/yagyarimal/556607) with interactive website pages quickly utilizing the intelligent markdown with a flash dashboard design template structure.